Non-Governmental Organizations Participations and Tactics in Kurdistan Regions Commission of Integrity Lawmaking - Smail, Rebaz Ali (International Journal of Social and Administrative Sciences, 2019)
The NGOs` role in policymaking is identified in the developed countries. Nevertheless, in the developing nations the role is not investigated properly. More importantly, the NGOs` tactics (insider and outsider) in the developing countries` literature unidentified systematically. Therefore, since the NGOs influenced the Kurdistan Palriament Commission of Integrity Law No 3 (2011). This paper attempts to investigate the NGOs` role in the law deliberations, to examine how NGOs participated in the law deliberations, and what tactics were used to influence the Kurdistan parliament. Accordingly, the study employed qualitative case study research design, and the data collected through face to face in-depth interview with 15 respondents including NGO members, parliament members, and experts. The interest groups theory adopted to analyze the NGOs` tactics and to compare the interest group theory`s tactics with the Kurdistan NGOs` tactics. Consequently, the paper found that the anti-corruption NGOs participated in law drafting, engaged in lawmakers` meetings, organized conferences and workshops, and audited parliamentary bill deliberations. Besides, the paper also found that the anti-corruption NGOs used insider and outsider tactics during their participation in the law deliberations. They have used partnership with lawmakers, presenting research results, writing letters and consultations, law drafting, training, and meeting with parliament members as insider tactics. Meanwhile, lobbying and media campaign were used as outsider tactics. The paper also declared that the Kurdistan NGOs used almost the same tactics which have been discussed in the interest group theory`s literature.